Pain control through selective chemo-axotomy of centrally projecting TRPV1+ sensory neurons - Sapio, Matthew R.; Neubert, John K.; LaPaglia, Danielle M.; Maric, Dragan; Keller, Jason M.; Raithel, Stephen J.; Rohrs, Eric L.; Anderson, Ethan M.; Butman, John A.; Caudle, Robert M.; Brown, Dorothy C.; Heiss, John D.; et al. (The Journal of clinical investigation, 2018)
Agonists of the vanilloid receptor transient vanilloid potential 1 (TRPV1) are emerging as highly efficacious nonopioid analgesics in preclinical studies. These drugs selectively lesion TRPV1+ primary sensory afferents, which are responsible for the transmission of many noxious stimulus modalities. Resiniferatoxin (RTX) is a very potent and selective TRPV1 agonist and is a promising candidate for treating many types of pain. Recent work establishing intrathecal application of RTX for the treatment of pain resulting from advanced cancer has demonstrated profound analgesia in client-owned dogs with osteosarcoma. The present study uses transcriptomics and histochemistry to examine the molecular mechanism of RTX action in rats, in clinical canine subjects, and in 1 human subject with advanced cancer treated for pain using intrathecal RTX. In all 3 species, we observe a strong analgesic action, yet this was accompanied by limited transcriptional alterations at the level of the dorsal root ganglion. Functional and neuroanatomical studies demonstrated that intrathecal RTX largely spares susceptible neuronal perikarya, which remain active peripherally but unable to transmit signals to the spinal cord. The results demonstrate that central chemo-axotomy of the TRPV1+ afferents underlies RTX analgesia and refine the neurobiology underlying effective clinical use of TRPV1 agonists for pain control.